2016
DOI: 10.1111/birt.12233
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Practices During the Confinement Period among Chinese, Malay, and Indian Mothers in Singapore

Abstract: Most Singapore mothers follow confinement practices, but the three Asian ethnic groups differed in specific confinement practices. Future studies should examine whether ethnic differences persist in later childrearing practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…China found that of 2,100 women, they spent about 18 hr lying in bed and one third of women did not have any outdoor activities during the puerperium (Liu et al, 2006). Other evidence including both quantitative and qualitative studies supports that this traditional postpartum practice is common in China (Chien, Tai, Ko, Huang, & Sheu, 2006;Fok et al, 2016;Liu, Maloni, & Petrini, 2014;Raven, Chen, Tolhurst, & Garner, 2007;Tien, 2004;Wang et al, 2008;Yeh, St John, & Venturato, 2014). Factors influencing women's postnatal practices are various including birth belief, education level, illness concept, respect for traditional culture and for elder family members (Liu et al, 2006;Wang, Wang, Zhou, Wang, & Wang, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…China found that of 2,100 women, they spent about 18 hr lying in bed and one third of women did not have any outdoor activities during the puerperium (Liu et al, 2006). Other evidence including both quantitative and qualitative studies supports that this traditional postpartum practice is common in China (Chien, Tai, Ko, Huang, & Sheu, 2006;Fok et al, 2016;Liu, Maloni, & Petrini, 2014;Raven, Chen, Tolhurst, & Garner, 2007;Tien, 2004;Wang et al, 2008;Yeh, St John, & Venturato, 2014). Factors influencing women's postnatal practices are various including birth belief, education level, illness concept, respect for traditional culture and for elder family members (Liu et al, 2006;Wang, Wang, Zhou, Wang, & Wang, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…CCs was most likely due to the cultural emphasis on the need for postnatal mothers to rest during the confinement period (4,7,9).We found some CCs that discouraged mothers from rooming-in with their babies at night and this is worrying because the baby's early feeding cues could easily be missed, leading to a reduction inbreastfeeding frequency and hence the amount of breast milk a mother produces.Sleeping in the same room as the baby or 24-hour rooming-in is crucial for night feeds, which is important for the establishment and continuation of breastfeeding (3) We also found that many mothers had restricted opportunities to access their babies both during the day and night, and this could explain why significantly more mothers in CCsonly fed expressed breast milk. With a growing body of evidence that feeding expressed breast milk might be different from feeding at the breast, this is an important finding.…”
Section: Discussionmentioning
confidence: 94%
“…During the confinement period, the mother would be assisted fully at her home by someone (or sometimes more than one person) -ensuring that she gets enough rest, providing the appropriate diet, caring for the newborn baby and ensuring she abides by confinement practices such askeeping warm(8). This usually means the motheravoids draughtsor taking showers for the whole month (4,7,9). This person was traditionally a close female relative (6)but practices have evolved to hiring a professional 'confinement lady' (yueso) who is considered an expert in the necessary diet and practices (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also present in the antenatal period and is influenced by multidimensional factors (Roll & Cheater, 2016). Factors affecting maternal attitude to breastfeeding include maternal characteristics, including age (Nouer et al, 2015), ethnicity (Linares et al, 2015), education level, occupational status (Ishak et al 2014), household income (Persad & Mensinger, 2008), parity (Buckles & Kolka, 2014), pregnancy intentions (Kost & Lindberg, 2015), caregivers (Fok et al, 2016), and previous exclusive breastfeeding experience (Mitra et al, 2004). Community empowerment, such as a good level of knowledge, can influence maternal attitudes on improving health status.…”
Section: Effect Of Community Empowerment On Nutritional Status Of Prementioning
confidence: 99%